Notes on Fruit Consumption of the Philippine Bulbul (Hypsipetes philippinus) and its quality as a seed disperser - Schabacker, Jen; Curio, Eberhard (Silliman Journal, 2022)
The Philippine Bulbul (Hypsipetes philippinus, Pycnonotidae) is, by virtue of its relative abundance, the most common frugivorous bird in primary and secondary forests in the West Visayas, Philippines. This paper compiles data on 49 tree species used for their fleshy fruits by the Philippine Bulbul. Additional more detailed ob-servations were made an one tree each of four fig (Ficus sp.) species as well as a number of other fruit-eating forest birds. Bulbuls feed in general on small fruits of up to 20 mm in diameter. Depending on tree species, they eat 66-82% of the fruits which they pluck from the source tree and drop only a minor proportion into the ground. Only less than 9-22% of fruits harvested are carried away from the source tree in the bird's beak. Since birds stay in the near vicinity of an ex-ploited tree, the fraction of fruits carried over long distances seems to be small. However, of those many seeds ingested on and near a source tree, a substantial fraction may be dis-persed over longer distances upon passing the gut. The bulbul benefits a fruiting tree through seed dispersal since it ingests all seeds by swallowing the fruits whole. Both this species and other frugivorous birds handle (eat, drop, carry) fruits in distinct ways irrespective of the tree species on which they feed. Thus, birds of up to eight species, including the bulbul, ex-ploiting the same fig species differ significantly from each other in the manner of handling mentioned. This translates into quality differences among those birds as seed dispersal agents. Being a generalist frugivore, and because of its abundance, the Philippine Bulbul may be among the most important seed dispersers in this region. Other forest birds, though being in part more specialized on fruits, appear to rank lower as seed dispersers for a number of reasons.